Kepolisian dan Hubungan Diplomatik dalam Penanganan Ecocide di Bireuen, Aceh - Setiawan, Roni; Fauzi, Fauzi; Iskandar, Iskandar (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Ecocide is a large-scale environmental crime that has become a serious concern throughout the world. This phenomenon not only damages the ecosystem, but also threatens human life that depends on natural resources. Handling environmental crimes has not been resolved until now on a global scale. Likewise in Bireuen district, Aceh province, Indonesia. The purpose of this study is to examine the role of the police and the dynamics of diplomatic relations in handling ecocide in Bireuen, Aceh. This research method uses a qualitative approach with the analytical knife of Critical Discourse Analysis (CDA) and direct involvement of researchers. The results of this study found that diplomatic relations need to be implemented for the readiness of the police and related institutions in Bireuen in handling the impacts of ecocide. Handling efforts need to be improved including the alertness of the police who collaborate with related institutions.